(untitled) (Superficies y Vacío, 2024)
This work presents a calculation of the electronic and optical properties of the family of high critical temperature superconductors (Tc > 90 K) Sm3xY3(1-x)Ba5Cu8O18 (Sm3xY3(1-x)58), para 0 < x < 1, as well as those of Y1Ba2Cu3O7 (Y123) and those of Sm1Ba2Cu3O7 (Sm123), carried out using the first principles method LAPW+lo (linearized augmented plane wave + local orbitals), within the DFT theory (density functional theory). The Density of Electronic States (DOS) and optical conductivity are calculated for four crystal structures generated by varying x (for x = 0; 1/3; 2/3; 1). The objective was determined. DOS (partial and total) and optical conductivity at low energies. In particular the effect of the f orbitals of Sm near the Fermi energy (Ef). It was found that by substituting Sm atoms for Y atoms, the total DOS is affected around Ef due to the contribution of the Sm f orbitals. When the system has two atoms of Y and one of Sm (Sm1Y258). The value of the total DOS in the Ef increases 547% with respect to the compound Y358. When the system has 2 atoms of Sm and one of Y (Sm2Y158), the value of the total DOS in the Ef increases 1043% with respect to the compound Y358. While in the case of Sm358, it increases 1432%. For Sm123 and Sm358 the optical conductivity presents a peak near the origin. While for Y358 it does not present any peak in conductivity and presents very low values near the origin. For the cases x = 1/3 and 2/3 we find that the conductivity is modified near the origin. The highest value occurs for the system containing two Sm atoms, this was at 0.14 eV.